2016
DOI: 10.1371/journal.pntd.0004903
|View full text |Cite
|
Sign up to set email alerts
|

A Primate APOL1 Variant That Kills Trypanosoma brucei gambiense

Abstract: Humans are protected against infection from most African trypanosomes by lipoprotein complexes present in serum that contain the trypanolytic pore-forming protein, Apolipoprotein L1 (APOL1). The human-infective trypanosomes, Trypanosoma brucei rhodesiense in East Africa and T. b. gambiense in West Africa have separately evolved mechanisms that allow them to resist APOL1-mediated lysis and cause human African trypanosomiasis, or sleeping sickness, in man. Recently, APOL1 variants were identified from a subset o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 88 publications
2
18
0
Order By: Relevance
“…These findings also correlate with some previous ones among which the identification of an Apolipoprotein L1 (APOL1) in a subset of Old World monkeys [15], [16], [17], [18], the demonstration of the in vitro lytic ability of serum and purified recombinant protein of an Apolipoprotein L1 (APOL1) ortholog from the West African Guinea baboon (Papio papio), which is able to lyse all subspecies of T. brucei including T. brucei gambiense [5].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…These findings also correlate with some previous ones among which the identification of an Apolipoprotein L1 (APOL1) in a subset of Old World monkeys [15], [16], [17], [18], the demonstration of the in vitro lytic ability of serum and purified recombinant protein of an Apolipoprotein L1 (APOL1) ortholog from the West African Guinea baboon (Papio papio), which is able to lyse all subspecies of T. brucei including T. brucei gambiense [5].…”
Section: Discussionsupporting
confidence: 89%
“…For instance, 3 distinct constitutive defense mechanisms against T. brucei have been detected by Black et al [2], in sera from sub-Saharan mammals other than primates that show a high level of resistance to African trypanosomes, and they reported that these mechanisms act together with parasite-specific antibody responses to control the severity of infection arising in the reservoir hosts [2]. In the same regard, some studies have also been carried out on some zoo primates [3], [4], [5]. The present study was targeting at investigating the presence of nonspecific factors against T. brucei brucei and T. congolense, in the sera of two species of Zoo Primates, Erythrocebus patas (Red patas monkey) and Chlorocebus tantalus (Tantalus monkey).…”
Section: Introductionmentioning
confidence: 95%
“…Hence, it seems that while multiple mechanisms have been acquired by various trypanosomes to block the lysosomal pore-forming catalytic activity of NHS, this activity itself is executed in large by a single factor, i.e., ApoL1. This finding itself has attracted scientific attention over the last years with respect to primate evolution ( 120 ), and has resulted in the findings that (i) ApoL1 is the common lytic factor in human, gorilla, and baboon primate sera ( 7 , 8 , 121 ), (ii) the chimpanzee, orangutan, and macaque, which are susceptible to all T. brucei subspecies, lack functional ApoL1 ( 121 ), and (iii) the baboon ApoL1 variant is capable of killing even T. b. gambiense and T. b. rhodesiense , as opposed to the human ApoL1 ( 122 , 123 ). The latter finding has prompted an attempt to generate genetically modified TLF transgenic livestock that would be able to resist all known pathogenic trypanosome species ( 122 ).…”
Section: Adaptations Of Animal Infective Trypanosomes To Human Hostmentioning
confidence: 99%
“…Of note, the T. brucei (sub-genus Trypanozoon) clade can be further divided into strictly animal infecting parasites (T. brucei brucei) and parasites able to infect also humans and higher primates, namely the zoonotic T. brucei rhodesiense and the anthroponotic T. brucei gambiense [19,20]. This is attributed to the fact that these latter parasites acquired the ability to resist trypanolytic molecular complexes, expressed by humans and higher primates as part of the innate immune system [20][21][22][23][24]. Due to this reason, and its implications for human medicine, the T. brucei clade has received greater attention and is better characterized, despite being it having a lower, though still potent, worldwide impact on veterinary economy, than for example T. congolense (Subgenus Nannomonas) or T vivax (Sub-genus Dutonella) [25].…”
mentioning
confidence: 99%